2022
DOI: 10.24093/awej/vol13no2.17
|View full text |Cite
|
Sign up to set email alerts
|

An Affective Approach to Teaching Literature: I Feel Therefore I am

Abstract: The present research paper seeks to ascertain whether students respond emotionally to literature—as it is argued that the emotions experienced during reading help interpret literary texts. To that end, the study departs from an investigation of students’ personal responses only to determine whether emotion-based responses exist in the EFL context, thus answering the central question that guides this work: do affective responses to literature exist? The stakeholders involved in this study are master-one, EFL st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…And these ten studies by (Al Sabiri & Kaymakamoğlu, 2019;Atek et al, 2020;Bunga Febriani et al, 2022;Fauziah, 2016;Granath, 2017;Jabeen & Sarifa, 2022;Ling & Chen, 2016;Resueňo & Ian Bel Resueňo, 2019;Suliman et al, 2019;Wahyuni et al, 2021), revealed that there are six main approaches employed by teachers in teaching literature, which are the information-based approach, moral-philosophical approach, paraphrastic approach, language based approach, reader response approach, and stylistic approach. Subsequently, four studies by Benonguil & Barnido (2022); Hernández (2020); Moustafa & Naima (2022) and Yimwilai (2015) suggested other teaching methods such as the experimental group approach, communicative approach, affective responses approach, and focus group discussion.…”
Section: Approaches Employed By Teachersmentioning
confidence: 99%
See 2 more Smart Citations
“…And these ten studies by (Al Sabiri & Kaymakamoğlu, 2019;Atek et al, 2020;Bunga Febriani et al, 2022;Fauziah, 2016;Granath, 2017;Jabeen & Sarifa, 2022;Ling & Chen, 2016;Resueňo & Ian Bel Resueňo, 2019;Suliman et al, 2019;Wahyuni et al, 2021), revealed that there are six main approaches employed by teachers in teaching literature, which are the information-based approach, moral-philosophical approach, paraphrastic approach, language based approach, reader response approach, and stylistic approach. Subsequently, four studies by Benonguil & Barnido (2022); Hernández (2020); Moustafa & Naima (2022) and Yimwilai (2015) suggested other teaching methods such as the experimental group approach, communicative approach, affective responses approach, and focus group discussion.…”
Section: Approaches Employed By Teachersmentioning
confidence: 99%
“…Through these activities, students will have a better understanding of literary texts, especially those who are weak in English. It is also a good way of helping them to pronounce the English words by reading aloud the literary texts in the class (Moustafa & Naima, 2022). Ling & Chen (2016) suggested group discussion and sharing sessions.…”
Section: Activities Conducted In Classroommentioning
confidence: 99%
See 1 more Smart Citation